Dalla materia ai pixel. Note sulla poesia visiva tra analogico e digitale - Silvia Pireddu (Ocula)
Visual poetry is a hybrid genre that, by combining images of different natures and texts, triggers a psychic reaction of involvement or estrangement. Typically multimodal, the genre evolves around matter and language. The repositioning in the digital world of many visual poets has introduced an additional, "augmented", dynamic and performative dimension. The paper describes works with an anglosaxon cultural background attesting to the transition to the digital and the appearance of a further "semantic charge". In particular The Last Vispo Anthology of Visual Poetry 1998-2008 (Seattle, 2012), thingsithought.today by Lauren Holden and Enigma2022 by Jim Andrews.